Role of SHGs and MFIs towards Women Empowerment and Reducing Gender Stereotypes in Uttarakhand, India - Kandpal, Vinay; Mehrotra, Rajat; Oli, Deep Chandra (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to analyze the role of micro finance institutions and Self Help Groups (SHGs) in the empowerment of people especially women living in rural areas through placements or job opportunities across different sectors thus removing gender stereotypes prevailing in society and removing the migration issue in Uttarakhand. Women in India earn a median gross salary of ₹196 per hour, 19% lower than₹242 for men, according to the latest Monster Salary Index. Wage inequalities are the highest in IT/ITES (26%) and manufacturing (24%), but even women-intensive sectors such as healthcare and social work show a steep pay gap (21%). BFSI fares the best, with men making just 2% more. The survey also finds that the earnings gap widens with higher skill level – from zero for semi-skilled work to 30% for highly skilled jobs. Building and enhancing financial literacy of the population, especially women, is imperative to sustain financial inclusion while ensuring women’s empowerment and attracting them towards Entrepreneurship and job prospects across different sectors not limited to those that were traditionally taken as job for women and men. To promote gender equality along with the entrepreneurial spirit, it is inevitable to finance women for various small and local start- ups. If the SHGs, SHG federations, promoters, banks and other agencies working works towards the quality of SHGs to evolve as member owned, managed and controlled institutions; provide an environment to access quality services from financial and non-financial agencies, the SHGs would significantly contribute to achieve the goals of financial inclusion and inclusive growth.